(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Tussah silk fibroin is a promising material for drug release because of protein component, biocompatibility, aqueous processability, and biodegradability. Tussah silk fibroin nanoparticles were self-assembled and prepared in this paper. Their appearances and sizes were modified by altering the volume ratios between tussah silk fibroin and ethanol. When 9 mL of ethanol was added, the average microsphere size was 184.52 nm and the scattered index was 0.2903. The tussah silk fibroin nanoparticles for controlled drug release was studied and the result showed that the time of drug release was significantly longer. The process of drug release was divided into rapid release in early stage and slow release in late stage. The target drug delivery can reduce the negative effects and improve the efficiency of the drug. As a result, it favors deeper investigation of tussah silk fibroin nanoparticles as drug carriers for controlled release of sensitive biologicals.